Edukasi Pemeliharaan Kesehatan Gigi di Pondok Pesantren Palembang - Hamid, Abu; Nurhayati, Masayu; Widodo, Yufen (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Background: Pesantren (Islamic boarding schools) are a unique heritage of Nusantara Islam that are found only in Indonesia. As traditional educational institutions, pesantren are not singular, but there are three typologies of pesantren that have developed to this day. These three typologies are salaf pesantren, modern pesantren, and the convergence of salaf and modern, also known as semi-modern. Among these three, the salaf pesantren has the lowest funding. The lack of dental and oral health facilities in the pesantren environment also contributes to inadequate maintenance of dental and oral health. Method: The target is to improve the knowledge and dental and oral health status of the students at Al Burhan pesantren. Results showed an 85% increase in knowledge among the students at Al Burhan pesantren, categorized as good, and the prevention of caries through fluoride varnish application (FTCP) to all students of Al Burhan pesantren. Conclusion: The implementation of community service activities.